Women Staff In Business Schools: An Exploratory Study - Jones, Deborah; Reilly, Amanda; Krisjanous, Jayne; Vasquez, Carla Rey (School of Management Working Papers, 2011)
This paper presents the findings of a study which aimed to identify equity issues in the working lives of women staff in a New Zealand university business school. A participatory action research methodology was adopted which includes several stages. This paper reports on the first two: focus groups and a survey. The findings suggest that over-work and lack of community are key issues. Some women feel disadvantaged in relation to male colleagues, while others reject this notion. The paper links challenges in carrying out the research to the findings themselves. Distinctive features of the project are the emphasis on overall quality of work life and the inclusion of all women staff (general/professional and academic).